Prevalence of non-O157 Shiga Toxin-producing E. Coli in Children and Calves in Al- Muthanna Province, Iraq - Ahmed Jarad; Kh. Al- Jeboori (مجلة الانبار للعلوم البيطرية)
The present study focus on non-O157 Shiga toxin-producing E. Coli (STEC), included a bacteriological study was subjected to provide additional information for non-O157 STEC prevalence in children and calves. Isolation by using selective culturing media (CHROMagar STEC and CHROMagar O157) from 127 children suffering from diarrhea and 133 calves in Al- Muthanna province. Characterization depends on culturing positive colony on MacConkey agar and Levin’s Eosin Methylene blue agar, staining single colony from the growth by gram stain, biochemical tests; Indole, the Methyl Red, Voges-Proskauer, Citrate test, Oxidase, Catalase, Urease, Motility, Kligler Iron and Api-20E, were done to confirm a diagnosis of non-O157 STEC, The reliable isolation as non-O157 STEC serotyping by specific latex agglutination test for the target non-O157 STEC (big six) serogroup (O26, O45, O103, O111, O121 and O145). The current study showed the prevalence of non-O157 STEC was 20 of out 127 (15.73%) in samples collected from children and 27 / 133 (20.30%) in calves samples in conclusion the Non-O157 STEC is an important cause of diarrhea in children, and calves; finally, the calves play an important reservoir for Non-O157 STEC.